The 1964 Coup in Brazil, through the pages of the Ultima Hora newspaper (UH) - Fidelis, Thiago [UNESP] (EDIPUCRS, 2023)
This study examines how the newspaper Ultima Hora (UH) portrayed the 1964 coup in its pages during the early months of that year. The research is significant because UH has a large readership in Brazil and takes a supportive position toward João Goulart’s government, unlike other printed newspapers. In contrast, opposition movements openly advocated for a military intervention to remove the current president, receiving significant support from the mainstream media, as evidenced in the extensive literature on the subject. As a result, this research argues that UH has consistently adhered to its political ideology since its establishment in 1951. It strongly defends the labor principles and policies associated with Getúlio Vargas, considering Goulart as a symbolic successor to Vargas. According to UH, civilian and military opposition factions vehemently opposed the establishment of a government that drew inspiration from this model, leading to attacks against the president based on this aspect. The refusal to accept the consolidation of such a government stemmed from their rejection of the principles it represented.
El Golpe de 1964 en Brasil, a través de las páginas del diario Ultima Hora (UH)
O Golpe de 1964, no Brasil, pelas páginas do jornal Ultima Hora (UH)
Keywords: Coup of 1964; João Goulart; Ultima Hora